Antioxidant Enzymes Eritrocitarias in Native People of High Altitude - Adriazola J., Marco (2008)
It was determined the levels of antioxidant enzymes: Glutathione Peroxidase (GPx), Superoxide Dismutase (SOD) and Catalase (CAT), and the concentratíon of Malondialdehyde (MDA) as an indicator of lipid peroxidatíon in erythrocytes of 60 apparently healthy people: 30 residents at high altitude (Cerro de Paseo, 4340 m) and 30 residents at sea level (Lima, 150 m). We found erythrocyte GPx levels higher in high altitude natives than in the sea level ones (p < .001). No statistically significant differencc was found between the val u es obtained for SOD in high altitude na ti ves and those of sea leveL The CAT activity was lower in subjccts of high altitude in relation to those of sea level (p < .001). High altitude native MDA levels also were lower than those obtained at sea level (p < .001). We concluded that Glutathione Peroxidase is the main antioxidant enzyme for the detoxification of H202 and that the formation of hydroperoxide in erythrocytes of high altitude inhabitants would be sufficiently neutraJized by this enzyme, judging by the lower level of TBARS found.